Activity and Characterization of ZnO Nanoparticles from Ethanol Extract of Plantago major L. as Antibacterial against Propionibacterium acnes - I Kadek Sudartayasa; Risyandi Anwar; Maya Dian Rakhmawatie (Fakultas Farmasi Universitas Andalas, 2025)
Acne infections are common in tropical regions such as Indonesia and are mainly caused by Propionibacterium acnes. Long-term use of antibiotics for acne treatment may lead to bacterial resistance, highlighting the need for safer natural antibacterial alternatives. Ethanol extract of broadleaf (Plantago major L.) has been reported to exhibit antibacterial activity, which can be enhanced through the application of nanotechnology in the form of zinc oxide nanoparticles (ZnO-NPs). Therefore, this study aims to synthesize and evaluate the antibacterial activity of ZnO-NPs derived from ethanol extract of broadleaf against P. acnes. The broadleaf extract was obtained through maceration with 96% ethanol, and ZnO-NPs were prepared by a precipitation method using zinc nitrate and zinc acetate precursors. The disc diffusion test results showed that 20 mg of ZnO-NPs acetate from broadleaf extract had strong antibacterial activity, with an inhibition zone of 18.11 ± 0.10 mm. The minimum inhibitory concentration of ZnO-NPs acetate from broadleaf extract is 0.078 mg/mL. The morphological characterization of ZnO-NPs acetate from broadleaf extract using Scanning Electron Microscopy-Energy Dispersive X-Ray (SEM-EDX) show a uniform granular particle shape with a size range of 200-228 nm. Based on the research results, the ZnO-NPs acetate from ethanolic extract of broadleaf has the potential to be an effective topical antibacterial alternative for treating acne infections. Based on these findings, ZnO-NPs synthesized from ethanol extract of broadleaf are expected to enhance antibacterial effectiveness and have potential as a safer and more effective topical antibacterial alternative for acne treatment